2010
DOI: 10.1007/s10554-010-9726-9
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial scar extent evaluated by cardiac magnetic resonance imaging in ICD patients: relationship to spontaneous VT during long-term follow-up

Abstract: Patients with ischemic cardiomyopathy have an increased risk for ventricular arrhythmia, since myocardial infarction can be the substrate for re-entrant arrhythmias. Contrast-enhanced cardiac magnetic resonance imaging (CMR) has proven to reliably quantify myocardial infarction. Aim of our study was to evaluate correlations between functional and contrast-enhanced CMR findings and spontaneous ventricular tachy-arrhythmias in patients with ischemic cardiomyopathy who underwent implantable cardioverter-defibrill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…During a follow-up period of 1184±442 days 68 monomorphic and 14 polymorphic types of ventricular tachycardia (VT) could be observed in 12 patients. Patients with monomorphic VT had larger scar volumes (25.3±11.3 vs. 11.8±7.5% of myocardial mass, than patients with polymorphic VT (19). This study indicates the role of CMR in identifying substrate for monomorphic VT. T wave alternans is a noninvasive method that predicts future tachyarrhythmias in various types of heart diseases (12, 13).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…During a follow-up period of 1184±442 days 68 monomorphic and 14 polymorphic types of ventricular tachycardia (VT) could be observed in 12 patients. Patients with monomorphic VT had larger scar volumes (25.3±11.3 vs. 11.8±7.5% of myocardial mass, than patients with polymorphic VT (19). This study indicates the role of CMR in identifying substrate for monomorphic VT. T wave alternans is a noninvasive method that predicts future tachyarrhythmias in various types of heart diseases (12, 13).…”
Section: Discussionmentioning
confidence: 60%
“…In our study, we used areas with an SI between 2 and 6 SD above SI of remote myocardium as peri-infarction zone. Bernhardt et al (19) studied the utility of CMR in predicting monomorphic VTs during followup. They enrolled 41 patients with ischemic cardiomyopathy and indication for ICD therapy underwent cine and late gadolinium enhancement CMR for quantification of left ventricular volumes, function and scar tissue before subsequent implantation of ICD device.…”
Section: Discussionmentioning
confidence: 99%
“…The infarct core provides anatomic boundary needed for sustained reentry. Infarct size/mass quantification by MRI has been shown to predict EPS-induced (9) and clinical VT (10,11,15). The peri-infarct zones are damaged but viable regions of myocardium which contribute to VT through slowing of conduction and uni-directional block due to altered refractory periods.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that infarct size is a better predictor of inducible VT than the left ventricular ejection fraction (9), highlighting the importance of the infarct substrate in the generation of VT. Infarct size measure by MRI has also been shown to be an independent predictor of mortality (10) and spontaneous VT (11). The surrounding border zones, also known as “gray zones”, are thought to be a heterogeneous mix of viable and non-viable myocardium and have been shown to correlate with post-MI mortality (12), clinical VT (13) and VT inducibility (14).…”
Section: Introductionmentioning
confidence: 99%
“…Stensaeth et al [50] reported the clinical characteristics of patients with suspected ST-elevation myocardial infarction and normal coronary arteries. Patients with monomorphic ventricular tachycardia (VT) were found to have larger scar volumes than patients with polymorphic VT, suggesting that CMR may be used for better risk stratification in patients with ischemic cardiomyopathy undergoing implantable cardioverter-defibrillator therapy [51]. Kino et al [52] compared a navigator free breathing 3D phase sensitive inversion recovery (PSIR) TurboFLASH sequence to an established 2D PSIR method and found more hyper-enhanced scars and larger scar volume with the 3D technique suggesting potential advantages for scar assessment.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%